2019
DOI: 10.1111/all.13949
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and clinical characteristics of autoimmune chronic spontaneous urticaria: Results of the PURIST Study

Abstract: Background: Autoimmune chronic spontaneous urticaria (aiCSU) is an important subtype of chronic spontaneous urticaria (CSU) in which functional IgG autoantibodies to IgE or its high-affinity receptor (FcεRI) induces mast cell degranulation and subsequent symptom development. However, it has not been tightly characterized. This study aimed to better define the clinical and immunological features and to explore potential biomarkers of aiCSU.Methods: This was a multinational, multicenter study of 182 CSU patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
182
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 176 publications
(217 citation statements)
references
References 47 publications
9
182
1
3
Order By: Relevance
“…Most CSU patients treated with omalizumab become symptom-free within the first month of their first injection. This is in line with type I autoimmunity, where anti-IgE rapidly binds free IgE, including IgE against autoantigens, and IgE/anti-IgE complexes bind autoallergens, thereby reducing MC degranu- [112][113][114] Diagnosis total auto-IgE and specific IgE to autoallergens 1 in type I [115], triple positivity: BHRA/BAT+ASST+WB/ELISA+ in type IIb [24,25] Disease activity/severity tends to be higher in type IIb [12, 14, 25, 111] 2 Disease duration tends to be longer in type IIb as shown in some [116,117] but not all [25] studies…”
Section: Type I and Type Iib Autoimmunity: Emerging Endotypes Of Chrosupporting
confidence: 66%
See 2 more Smart Citations
“…Most CSU patients treated with omalizumab become symptom-free within the first month of their first injection. This is in line with type I autoimmunity, where anti-IgE rapidly binds free IgE, including IgE against autoantigens, and IgE/anti-IgE complexes bind autoallergens, thereby reducing MC degranu- [112][113][114] Diagnosis total auto-IgE and specific IgE to autoallergens 1 in type I [115], triple positivity: BHRA/BAT+ASST+WB/ELISA+ in type IIb [24,25] Disease activity/severity tends to be higher in type IIb [12, 14, 25, 111] 2 Disease duration tends to be longer in type IIb as shown in some [116,117] but not all [25] studies…”
Section: Type I and Type Iib Autoimmunity: Emerging Endotypes Of Chrosupporting
confidence: 66%
“…Rates of concomitant autoimmune diseases tend to be higher in type IIb [25,[118][119][120][121] Rates of concomitant allergic diseases might be higher in type I [119] Total IgE levels low in type IIb and normal or high in type I [14,25] Basopenia rates might be higher in type IIb [24, 111] 2 Eosinopenia rates tend to be higher in type IIb [122] C-reactive protein levels may be higher in type IIb [25,123] ANA positivity rates may be higher in type IIb [124] Responder rates to sgAHs may be lower in type IIb [122][123][124][125] Responder rates to omalizumab high in type I [28] and low in type IIb [62,122,126] Speed of response to omalizumab slow in type IIb [127] Immunosuppressive therapy can be effective in type IIb [128-134] 3 TPO, thyroperoxidase; TG, thyroglobulin; TF, tissue factor; IL, interleukin; dsDNA, double-stranded DNA; BHRA, basophil histamine release assay; BAT, basophil activation test; ASST, autologous serum skin test; WB, Western blot; ELISA, enzyme-linked immunosorbent assay; CRP, C-reactive protein; ANA, antinuclear antibodies; sgAHs, second-generation antihistamines. 1 Measured by ELISA or radioimmunoassay.…”
Section: Type I and Type Iib Autoimmunity: Emerging Endotypes Of Chromentioning
confidence: 96%
See 1 more Smart Citation
“…These findings show that the patients exhibiting the features of autoimmune CSU with type IIb autoimmunity (positive in vivo reactivity (ASST), positive in vitro basophil reactivity (BHRA) and presence of IgG autoantibodies against FcεRI) are less likely to completely respond to omalizumab [53,54]. However, considering that only 8% of the patients in the PURIST study fulfilled all three criteria, novel clinical or laboratory biomarkers of response to omalizumab are still needed [53]. The clinical and laboratory predictors of response to omalizumab in patients with CSU are given in Table 3.…”
Section: Omalızumab: From Development To Current Challengesmentioning
confidence: 92%
“…Studies investigating the factors associated with response to omalizumab have revealed that patients with a positive basophil histamine release assay (BHRA), a positive autologous serum skin test (ASST), lower baseline basophil FcεRI expression, lower IgE levels, and a lower ratio of 4-week/baseline IgE are more likely to show no response or a slow response [46][47][48][49][50][51][52]. These findings show that the patients exhibiting the features of autoimmune CSU with type IIb autoimmunity (positive in vivo reactivity (ASST), positive in vitro basophil reactivity (BHRA) and presence of IgG autoantibodies against FcεRI) are less likely to completely respond to omalizumab [53,54]. However, considering that only 8% of the patients in the PURIST study fulfilled all three criteria, novel clinical or laboratory biomarkers of response to omalizumab are still needed [53].…”
Section: Omalızumab: From Development To Current Challengesmentioning
confidence: 99%